2016
DOI: 10.3390/molecules21111473
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Formulation of Thermosensitive Drug Carrier for Temperature Triggered Delivery of Naproxen Sodium

Abstract: Nanospheres and microspheres are known as a multipurpose compounds and are used in various branches of science. Recent controlled delivery systems for drugs are also based on poly-micro and nanospheres. In our study we describe an investigation of the influence of thermosensitive polymer N-isopropylacrylamide (NIPA) on the release of the drug naproxen sodium (NS) with a hydrogel hydroxypropyl methylcellulose (HPMC) base. The hydrodynamic diameter (D H ) of the obtained polymer was measured by using dynamic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…The release profiles obtained in former experiments had a growing pattern similar to the logarithmic graph, similarly to the former experiments [ 24 ]. The lowest degree of release at 22 ± 0.5 °C of the active substance was found in AK2, and it may have been ascribed to the type of used crosslinker and comonomer.…”
Section: Discussionsupporting
confidence: 75%
“…The release profiles obtained in former experiments had a growing pattern similar to the logarithmic graph, similarly to the former experiments [ 24 ]. The lowest degree of release at 22 ± 0.5 °C of the active substance was found in AK2, and it may have been ascribed to the type of used crosslinker and comonomer.…”
Section: Discussionsupporting
confidence: 75%
“…[ 30 ]. The influence of the formulation based on N -isopropylacrylamide and hydroxypropyl methylcellulose thermosensitive hydrogel for the naproxen sodium release was investigated [ 31 , 32 , 33 , 34 ]. Release tests showed that modification of the cross-linker type influenced the properties of synthesized polymeric particles obtained via surfactant free precipitation polymerization [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic diameter of the particles was examined via DLS (dynamic light scattering) what enabled, in limited field, evaluation of polydispersity of prepared samples of rehydrated dispersions of liposomal fraction according to procedures performed formerly in our department [51]. The measurement of hydrodynamic diameter of the particles was carried out using the Zetaseizer Nano ZS ZEN3600 analyzer from Malvern (UK).…”
Section: Methodsmentioning
confidence: 99%